2023
DOI: 10.1021/acs.langmuir.2c02688
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Protein Delivery of Ionic Liquid-Mediated HMGB1 Coating on Titanium Implants

Abstract: Strategies for modifying titanium (Ti) implant surfaces are becoming increasingly popular to enhance osseointegration during acute and inflammatory healing stages. In this study, two dicationic imidazolium-based ionic liquids (IonLs) containing phenylalanine and methionine anions (IonL-Phe(1,10-bis(3methylimidazolium-1-yl)decane diphenylalanine) and IonL-Met-(1,10-bis(3-methylimidazolium-1-yl)decane dimethionine)) were investigated to stably deliver exogenous proteins on Ti to promote osseointegration. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…Previous in vitro and in silico research from our lab validated that the IonL used in this study could pre-immobilize HMGB1 in a biologically active conformation . Considering the different HMGB1 coating formulations, Ti-IonL-DS samples demonstrated the thickest fibrous encapsulation after 14 days compared to all other treatment groups (Figure ).…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…Previous in vitro and in silico research from our lab validated that the IonL used in this study could pre-immobilize HMGB1 in a biologically active conformation . Considering the different HMGB1 coating formulations, Ti-IonL-DS samples demonstrated the thickest fibrous encapsulation after 14 days compared to all other treatment groups (Figure ).…”
Section: Discussionsupporting
confidence: 55%
“…Previous in vitro and in silico research from our lab validated that the IonL used in this study could pre-immobilize HMGB1 in a biologically active conformation. 15 Considering the different HMGB1 coating formulations, Ti-IonL-DS samples demonstrated the thickest fibrous encapsulation after 14 days compared to all other treatment groups (Figure 1). Correspondingly, histological results showed an increased area density % of inflammatory cells for Ti-IonL-DS samples at both 2 and 14 days and demonstrated that these tissues were potentially exposed to a particular irritant (Figure 2) compared to all other treatment groups.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations